Building an Implementation Strategy for Community-Based Rehabilitation for Mental Health in Colombia - Rojas-Andrade, R (Wolters Kluwer Health, 2024)
Introduction: Scientific evidence indicates that the community-based rehabilitation (CBR) model is recommended for recovery from mental disorders. However, this approach encounters barriers and often lacks implementation strategies. Aim: The aim of this study was to create a strategy for the implementation of CBR for mental health in Colombia through the identification of barriers and facilitators, together with the expected outcomes, from the perspective of mental health decision-makers in Colombia. Methods: This study adopts a qualitative descriptive approach, using focus group data collection methods and thematic analysis to code and analyze the data. Results: A total of 208 individuals participated in the study, including mental health decision-makers and health care professionals. Intersectoral collaboration, contextualization, financial resources, and community commitment and autonomy were identified as barriers and facilitators. The element that was considered a priority for successful implementation was the contextualization of strategies. Conclusions: CBR needs to be strengthened through implementation science if these strategies are to be successfully developed and implemented in various contexts. © 2024 JBI. Unauthorized reproduction of this article is prohibited.